MR Neurography of Neuromas Related to Nerve Injury and Entrapment with Surgical Correlation - Chhabra, A.; Williams, E.H.; Wang, K.C.; Dellon, A.L.; Carrino, J.A. (American Journal of Neuroradiology, 2010)
SUMMARY: MR imaging of peripheral nerves has been described in relation to abnormalities such as nerve injury, entrapment, and neoplasm. Neuroma formation is a known response to peripheral nerve injury, and here we correlate the MRN appearance of postinjury neuroma formation with intraoperative findings. We also present the MR imaging features of surgical treatment with a synthetic nerve tube and nerve wrap on postoperative follow-up imaging. MRNMR neurographyNICneuroma in continuitySPACEsampling perfection with application optimized contrasts by using different flip angle evolutionsSPAIRspectral adiabatic inversion recoverySTIRshort tau inversion recovery